Predifferentiated GABAergic Neural Precursor Transplants for Alleviation of Dysesthetic Central Pain Following Excitotoxic Spinal Cord Injury - Lee, Jeung Woon; Jergova, Stanislava; Furmanski, Orion; Gajavelli, Shyam; Sagen, Jacqueline (Frontiers in Physiology, 2012)
Intraspinal quisqualic acid (QUIS) injury induce (i) mechanical and thermal hyperalgesia, (ii) progressive self-injurious overgrooming of the affected dermatome. The latter is thought to resemble painful dysesthesia observed in spinal cord injury (SCI) patients. We have reported previously loss of endogenous GABA immunoreactive (IR) cells in the superficial dorsal horn of QUIS rats 2 weeks post-injury. Further histological evaluation showed that GABA-, glycine-, and synaptic vesicular transporter VIAAT-IR persisted but were substantially decreased in the injured spinal cord. In this study, partially-differentiated GABA-IR embryonic neural precursor cells (NPCs) were transplanted into the spinal cord of QUIS rats to reverse overgrooming by replenishing lost inhibitory circuitry. Rat E14 NPCs were predifferentiated in 0.1 ng/ml FGF-2 for 4 hrs prior to transplantation. In vitro immunocytochemistry of transplant cohort showed large population of GABA-IR NPCs that double labeled with nestin but few co-localized with NeuN, indicating partial maturation. Two weeks following QUIS lesion at T12-L1, and following the onset of overgrooming, NPCs were transplanted into the QUIS lesion sites; bovine adrenal fibroblast cells were used as control. Overgrooming was reduced in >55.5% of NPC grafted animals, with inverse relationship between the number of surviving GABA-IR cells and the size of overgrooming. Fibroblast-control animals showed a progressive worsening of overgrooming. At 3 weeks post-transplantation, numerous GABA-, nestin-, and GFAP-IR cells were present in the lesion site. Surviving grafted GABA-IR NPCs were NeuN+ and GFAP-. These results indicate that partially-differentiated NPCs survive and differentiate in vivo into neuronal cells following transplantation into an injured spinal cord. GABA-IR NPC transplants can restore lost dorsal horn inhibitory signaling and are useful in alleviating central pain following SCI.